Determination of Germination and Emergence Performance of Hemp (Cannabis sativa L.) Seeds at Different Maturity Stages - Güngör Yılmaz; Cebrail Yıldırım; Nurullah Dursun Gür (Turkish Journal of Agriculture: Food Science and Technology)
Seed maturation in hemp is not homogeneous, and the harvest is done when the seeds are 70-80% mature. This study was carried out to determine the germination and emergence performance of hemp (Cannabis sativa L.) seeds at different maturation stages. Mature, semi-mature and immature seeds were used as material in the study. The study was carried out as two separate experiments, germination and emergence. The germination test was carried out in petri dishes and the emergence test in viols. Both experiments were carried out according to the randomized complete block design with 3 replications. Germination rate (%), shoot and root length (mm), shoot and root fresh weight (mg plant-1) and shoot and root dry weight (mg plant-1) parameters were investigated in the germination study. In the emergence study, the emergence rate (%), seedling and root length (mm), seedling and root fresh weight (mg plant-1), and seedling and root dry weight (mg plant-1) values were examined. In the germination study, semi-mature seeds germinated but did not develop. Therefore, no data could be obtained from other parameters except germination rate. In germination study, germination rate varied between 6.67 and 84.67%, shoot length 27.2-38 mm, root length 39.4-50.8 mm, shoot fresh weight 30.66-49.89 mg plant-1, root fresh weight 4.32-7.69 mg plant-1, shoot dry weight 3.25-7.99 mg plant-1, root dry weight 0.68-2.03 mg plant-1. In the emergence study, emergence rate ranged between 5.18-82.69%, shoot length 68-136.4 mm, root length 37.4-69.6 mm, shoot fresh weight 60.33-154.80 mg plant-1, root fresh weight 27.30-46.73 mg plant-1, shoot dry weight 3.97-10.24 mg plant-1, root dry weight 2.61-5.43 mg plant-1. In both experiments, the highest values obtained from all the examined traits were obtained from mature seeds. In both studies, the highest values were obtained from mature seeds for all traits examined. Semi-mature and immature seeds gave similar results in terms of the traits examined.